Research on Brand Positioning Strategy and Brand Extension Strategy of Platform Enterprises——Taking TikTok as an Example - Chen, Xiaoxuan; Liang, Zilin (Transactions on Economics, Business and Management Research, 2024)
Platform enterprises rely on a new generation of information technology such as big data, cloud computing, and the Internet of Things to provide a digital platform for both supply and demand sides and facilitate transactions. As a result of ongoing technological advancement in this field in recent years, more and more platform companies become known to a wider public. Among them, TikTok is undoubtedly one of the most successful representative enterprises. TikTok adopts a targeted approach to brand positioning, establishes the target user group as young people, and extends the brand through brand ecological extension, expansion of overseas markets, and cooperation in marketing activities. TikTok's brand positioning and brand extension strategies are taken as the research object in this paper. The SWOT model is also used to analyze the advantages and disadvantages of the corporate strategy in terms of communication channels and content, as well as the opportunities and threats it faces in the macro-political and economic environment. At the same time, solutions are proposed to improve user experience, expand domestic and foreign markets, and build an ecosystem.